2008
DOI: 10.1093/bja/aem371
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic control of the puncture level for lumbar neuraxial block in obstetric anaesthesia

Abstract: The observed differences between clinical and ultrasonic identification of spinal puncture level highlight the potential for serious complications associated with the performance of neuraxial blocks above the spinous process of L3 in the parturient. With the increase in popularity of techniques involving puncture of the dura mater for labour anaesthesia, we feel that awareness of this risk is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 16 publications
8
46
0
10
Order By: Relevance
“…It has been shown repeatedly that clinical estimation of the lumbar intervertebral level using surface landmarks, such as the intercristal line, is inaccurate. [15][16][17][18][19][20][21] Our results are consistent with previous studies in that, when an error does occur, the actual intervertebral level tends to be higher than presumed, rather than lower. [16][17][18][19][20][21] It should be noted, however, that ultrasonographic determination of intervertebral level has not been fully validated against more definitive imaging methods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been shown repeatedly that clinical estimation of the lumbar intervertebral level using surface landmarks, such as the intercristal line, is inaccurate. [15][16][17][18][19][20][21] Our results are consistent with previous studies in that, when an error does occur, the actual intervertebral level tends to be higher than presumed, rather than lower. [16][17][18][19][20][21] It should be noted, however, that ultrasonographic determination of intervertebral level has not been fully validated against more definitive imaging methods.…”
Section: Discussionsupporting
confidence: 90%
“…[15][16][17][18][19][20][21] Our results are consistent with previous studies in that, when an error does occur, the actual intervertebral level tends to be higher than presumed, rather than lower. [16][17][18][19][20][21] It should be noted, however, that ultrasonographic determination of intervertebral level has not been fully validated against more definitive imaging methods. 19,22 Second, the LP scan generally affords better visibility of the LF/D and the PVB than the TM scan, an observation that was also made by Grau et al 23 The interspinous space is narrowed by the anatomic changes of aging (loss of vertebral height, osteophyte formation, and decreased ability to flex the lumbar spine), 3 and this can make it challenging to visualize the LF/D or the PVB on the TM scan.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies demonstrated accuracy in 29-59% of subjects when attempting to identify lumbar interspaces by palpation [3][4][5][6][7][8][9] . Our success rate (67%) was higher than those smaller size studies.…”
Section: Discussionmentioning
confidence: 99%
“…Broadbent et al 6 assessed the accuracy of palpation using MRI in a study of 100 patients. Many studies have compared palpation to ultrasound imaging [7][8][9][10] . With lumbar radiograph as the standard, Furness et al 7 showed that the correct interspace was identifi ed in 71% of 50 cases using ultrasound, compared with a 30% success rate with palpation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation